Quemar las naves: juegos novelescos de Alejandro Cuevas - Gutkowska, Katarzyna Zofia (Romanica Silesiana)
While trying to comment on Quemar las naves of Alejandro Cuevas, it is impossible not to notice the intricate net of tropes and means which makes it one of the most noteworthy examples of contemporary Spanish narratives. Written with great attention to details, structured with astonishing precision and based on multiple contrasts, the novel does not desist from surprising its reader. It seems, for example, paradoxical that a postmodernist story about the disintegration of a traditional poet’s life can be so perfectly coherent in its form, diligently organized, and divided into chapters and subchapters arranged alphabetically. Furthermore, the novel falls outside any unequivocal interpretation due to the author’s incessant trifling with mythological allusions, the wittiness and sharpness of his obliquely slipped insights concerning today’s culture and the status of literature, the introduction of playful ambiguity, and the unspecified space-time textual frame. Apart from that, Quemar las naves constitutes a kind of genealogical guessing game, as it contains elements of various genres and, thus, it cannot be analysed only within the constricting traditional genre classifications. All in all, Quemar las naves may be perceived as a kind of never-ending toying with literary conventions and with the readers’ expectations. Key words: Alejandro Cuevas, contemporary Spanish novel, 21st century Spanish narrative.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />